Ultrasound-Guided Comparison of Psoas Compartment Block and Supra-Inguinal Fascia Iliaca Compartment Block for Pain Management in Pediatric Developmental Dysplasia of Hip Surgeries - Quan, Junjun; Yang, Shujun; Chen, Yuchao; Chen, Kai; Yu, Siyuan (Frontiers in Pediatrics, 2022)
Background: The aim of this study was to compare psoas compartment block (PCB) and supra-inguinal fascia iliaca compartment block (SFIB) in terms of pain management and the need for additional systemic analgesia in the perioperative phase of developmental dysplasia of the hip (DDH). Materials and Methods: Sixty pediatric patients were randomized into the PCB group and the SFIB group. The Numeric Rating Scale (NRS) pain scores were used to assess postoperative pain during the initial 24 hours after extubation. Sufentanil consumption, patient-controlled analgesia (PCA) demands, and complications were also recorded. Results: The NRS pain scores were significantly lower in the PCB group than in the SFIB group at 0, 4, 8, 12 and 24 hours after extubation (all P ˂ 0.01). Postoperatively, 13.8% of patients in the PCB cohort received additional administration of sufentanil, in contrast to 63.3% of the SFIB cohort (P ˂ 0.01). In the PCB group, 0 (0-0) mcg/kg sufentanil was administered, while in the SFIB group 0.1 (0-0.2) mcg/kg (P ˂ 0.01). In addition, the PCB group had fewer PCA demands than the SFIB group within the initial 24 hours (P ˂ 0.01). It took less operating time to achieve SFIB as compared to PCB (P ˂ 0.01). No adverse events related to two techniques were recorded. Conclusions: PCB provided a better perioperative pain management in pediatric patients with the DDH surgeries compared to SFIB. It also reduced the need for supplementary systemic analgesia.